Analysis of Work-Life Balance Factors in Influencing Work Enthusiasm Mediated by Stress Management - Kartini, Tri Mulyani; Heriyanti, Sinta Sundari (DPPM Universitas Pelita Bangsa, 2023)
This study aims to analyze the work life balance factor in influencing work enthusiasm, stress management affects work enthusiasm, worklife affects stress management and worklife balance affects work enthusiasm mediated by stress management as an intervening variable. In this study using quantitative methods and conducting questionnaire distribution techniques to 108 respondents. From the results of questionnaire data processing that has gone through the validity test (convergent validity), reliability test, R square test, model fit test, F square test, path coefficient (bostrapping test), path coefficient, shows that the positive hypothesis results are significant. The results of the data analysis concluded that 1) worklife balance has a significant effect on morale, 2) stress management has a significant effect on morale, 3) worklife balance has a significant effect on stress management 4) worklife balance has a significant effect on morale mediated by stress management as an intervening variable.